Reversible Inactivation of the Bed Nucleus of the Stria Terminalis Prevents Reinstatement But Not Renewal of Extinguished Fear1,2,3 - Goode, Travis D. (eNeuro, 2015)
The extinction of conditioned fear is labile. For example, fear to an extinguished conditioned stimulus (CS) returns after presentation of an aversive stimulus (“reinstatement”) or a change in context (“renewal”). Substantial research implicates the bed nucleus of the stria terminalis (BNST) in the stress-induced relapse of extinguished behaviors, such as in instrumental drug seeking, but its role in the relapse of extinguished fear responses is not clear. Here, we explored the role of the BNST in both the reinstatement and renewal of fear, two forms of relapse that are differentially triggered by stress. In Experiment 1, rats received pairings of an auditory CS and footshock unconditioned stimulus (US) followed by an extinction procedure. After extinction, rats received an unsignaled US to reinstate fear to the extinguished CS. Twenty-four hours later, they were infused with either muscimol or vehicle into the BNST immediately prior to a CS retrieval test. In Experiment 2, rats were conditioned and extinguished in two distinct contexts. Twenty-four hours after extinction, the rats were infused with muscimol, NBQX, or vehicle immediately prior to a CS retrieval test in either the extinction context or a different (but familiar) context. In both experiments, freezing behavior served as the index of conditioned fear. The results revealed that BNST inactivation prevented reinstatement (Experiment 1), but not renewal (Experiment 2), of conditioned freezing to the extinguished CS. Hence, the BNST is critical for the reinstatement of extinguished fear in an aversive context, but not for the contextual retrieval processes that mediate fear renewal.